IC 6661 Mining Methods And Costs At Fresnillo, Zacatecas, Mexico ? Introduction - A. Livingston (The National Institute for Occupational Safety and Health (NIOSH), 1932)
This paper on mining practice at the Fresnillo silver mines is one of a series being prepared by the Bureau of Mines on mining practices, methods, and costs in the various mining districts of North America. Two classes of ore are produced at Fresnillo. A low-grade oxidized silver ore; end a complex-base sulphide are containing gold, silver, lead, zinc, and copper. This paper is confined to a discussion of operations relating to the production of oxidized silver ores. To date, more than 10 Million tons of this ore rave been mined. The present (June, 1931) daily production is 2,000 tons of ore, and approximately 600 men are employed in the mining operations.